PENGARUH FINTECH TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH - Muhammad Ma’ruf (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2021)
This study aims to determine the effect of fintech on the financial performance of Islamic banking. The type of research used in this research is descriptive research with a quantitative approach. The population in this study are all financial reports that have been published by Islamic banks that have started using fintech, namely BNI Syariah Bank, BRI Syariah Bank, Mandiri Syariah Bank, BCA Syariah Bank, Bukopin Syariah Bank and BJB Syariah Bank for the 2016-2018 period. Based on the purposive sampling method, the sample used in this study is Islamic Commercial Banks that have used fintech services such as Internet Banking, Mobile Banking, SMS banking, and Phone Banking and published annual financial reports from time to time during the research period, namely from 2016 -2018. Data management using SPSS. The survey results show that FinTech has an effect on financial performance (ROA, ROE, BOPO, CAR, FDR). The more sophisticated Fintech services in the field of Islamic finance will be, the more important it is for the financial performance of Islamic banks